Polimorfisme Gen UCP2 Dan Kadar H2O2 Terhadap Variasi CEC Sebagai Prediktor Aktivasi Endotel Pada Pasien Stroke - M.Nur FAFA; Djanggan Sargowo; Achdiat Agoes; Wiwit Nurwidyaningtyas (Jurnal Kardiologi Indonesia, 2014)
Research Background. Stroke as brain vascular disorder that can be ruptured vascular commonly referred to as a bleeding stroke or ischemic stroke may be due to cerebral arterial thrombosis as a final impact the progression of atherosclerosis, especially in the area of branching blood vessels. Atherogenesis related to endothelial dysfunction as a consequence shear stress exposure leads endothelial cells undergo premature senescence and activation of endothelial than occur endothelial detachment from the basement membrane as a circulating endothelial cells (CEC). Mechanism shears stress on endothelial activation can not be separated from the increased production of hydrogen peroxidase (H2O2), which will activate the PPAR-? then increase levels of free fatty acids are capable of modulating the uncoupling protein 2 (UCP 2) gene as a compensation for lowering of free fatty acids.Reseach Methods and Results. Researchers used 40 subjects were classified into two categories on a range of healthy and sick, who then performed blood sampling edge for lipid profile analysis, CEC using flowcytometry, H2O2 measurement with ELISA techniques and DNA isolation followed by PCR procedures with the Genomic DNA that has been extracted from blood samples amplified with the 5’-GCT GCT CAC AGG TCT GCC AC-3’sebagai forward primer and 5’-AGG CGT CAG GAG ATG GAC CG-3’sebagai reverse primer (Sesti et al, 2003; Oktavianthi et al, 2012). Genotype (-866) AA is characterized by fragments of 363 bp cutting results Mlu1 sites, whereas genotypes (-866) GG marked on fragments of 295 bp and 68 bp. The equipment used was a thermal cycler (Gene Amp® PCR System 9700 [Applied Biosystems, Foster City, CA, USA]). Results showed thatConclusion. CEC in the group sick 3 times higher than the healthy group as well as the levels of H2O2, but the two groups are not found polymorfism in both groups. Similarly, from the analysis of UCP2 gene allele frequencies between groups of stroke was not significantly different from the control group, this means yet certain UCP2 gene predispose and contribute to the pathogenesis of stroke.